p16 INK 4a and Ki-67 expression in human papilloma virus-related head and neck mucosal lesions. - Elif, Sibel; Sengüven, Burcu; Peter, Jens; Peter, Hans (Investigación Clínica, 2015)
Human papilloma virus (HPV) is postulated as a risk factor in the etiology of some specific mucosal pathologies in the head and neck regions. Despite the frequent use of p16 as a surrogate marker for HPV-infection, there is still controversy with respect to its reliability. This study has been undertaken to assess the potential role of p16 INK4a and Ki-67 expression in HPV-related lesions. The study was conducted on 71 specimens of oral, tonsillar and laryngeal lesions which comprised 25 dysplasia and 46 papilloma specimens. Specimens were immunohistochemically stained for p16INK 4a and Ki-67 proteins. HPV DNA was determined by one step multiplex polymerase chain reaction. HPV DNA was detected in 33.8% of all lesions. Tonsil and larynx lesions showed significant differences with oral lesions for HPV positivity (p<0.001). p16 over-expression was seen in 56.5% of papilloma and 60% of dysplasia specimens. HPV status showed a positive correlation with p16 INK 4a INK 4a expression in tonsillar dysplasias (p<0.001). p16 expression may have a value as a marker in high risk HPV induced dysplasias, but not in low risk infected lesions. The proliferation index is not related to HPV-induced le INK 4a sions and may be evaluated as an independent marker in head and neck premalignantlesions. INK4A